Comparison of echocardiography and 64‐slice spiral computed tomography in the diagnosis of congenital heart disease in children. Issue 3 (15th October 2018) - Mei, Mei; Nie, Jing; Yang, Zhan Shuang; Sun, Hua Wei; Wang, He; Kang, Xiao Ming
Abstract: The diagnosis of congenital heart disease in children has been an issue in the medical community. Timely diagnosis and treatment can provide a greater guarantee for children's healthy growth. In recent years, there have been more and more studies on the diagnosis of congenital heart disease in children. This paper compares the advantages and disadvantages of echocardiography and 64‐slice spiral computed tomography (CT) in the diagnosis of congenital heart disease in children. In clinical trials, we also tested 64 patients with spiral computed tomography (SCT) and transthoracic echocardiography (TTE) detection of patients and then confirmed the accuracy of the diagnosis by the surgical methods. The two methods of detection, the rate of missed diagnosis, and the rate of misdiagnosis were counted. Through the test results and pathological diagnosis results, the diagnostic accuracy of the two methods were all above 90%, each with its own advantages and disadvantages. The sensitivity of echocardiographic in detecting intracardiac structure abnormalities was relatively high, but when the diagnosis of extracardiac structural abnormalities less than 64‐slice spiral CT method, misdiagnosis of TTE was mainly due to extracardiac vascular malformations. Therefore, it is recommended to combine the two methods to improve the diagnosis of congenital heart disease in children.